1974
DOI: 10.1037/h0036716
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between values, social class, and duration of psychotherapy.

Abstract: The relationship between values, social class, and duration of psychotherapy of patients and therapists at a moderate cost outpatient clinic in New York City was investigated. Values were measured by the following scales: Strong Vocational Interest Blank, Ways to Live scale, Study of Values, and the Optimal Personality Integration Scale. Lower-class patients tended to be more authoritarian-submissive than upper-class patients. The significant linear relationship indicated that the lower the social class and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

1981
1981
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 9 publications
2
7
0
Order By: Relevance
“…As early as 1974, researchers began to address social class and counseling (Lorion, ; Pettit, Pettit, & Welkowitz, ; Sladen, ; Sue & Sue, ); however, these ideas were not incorporated significantly for almost three decades. Since 2000, researchers have begun to revisit social class (Liu, ) and discuss the impact social class has on people's experiences.…”
Section: Impact Of Social Classmentioning
confidence: 99%
“…As early as 1974, researchers began to address social class and counseling (Lorion, ; Pettit, Pettit, & Welkowitz, ; Sladen, ; Sue & Sue, ); however, these ideas were not incorporated significantly for almost three decades. Since 2000, researchers have begun to revisit social class (Liu, ) and discuss the impact social class has on people's experiences.…”
Section: Impact Of Social Classmentioning
confidence: 99%
“…How class is experienced within the therapeutic encounter is shaped by a number of factors, including: perceived role power (Totton, ); a sense of powerlessness that relates to clients’ personal histories (Balmforth, ); the quality of the relationship (Beckham, ; Isaac, ); initial impressions and assumptions (Liu, ); the use of language (Sembi, ); dress and appearance (Segal et al., ); and self‐disclosure (McGuinness, ). Furthermore, client/therapist social class disparity (including values) was shown to impact on therapy in one of two ways: creating either increased tension, as remarked upon by Daniels and Trier (), resulting in premature endings (Rokeach, ); or increased dependency prolonging therapy (Pettit, Pettit & Welkowitz, ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, disputing hypothesis (1), Scharf stein, Taube and Goldberg (1977) reported that, nationally, 84% of the federally funded community mental health center clientele were persons who had annual incomes less than $10,000. With respect to hypothesis (2), Pettit, Pettit and Welkowitz (1974) failed to find any overall connection between length of treatment and social class.…”
Section: Same-race Versus Interracial Counseling Dyadsmentioning
confidence: 77%